Assessing Ecosystem Services and Multifunctionality for Vineyard Systems - Winkler, Klara J.; Viers, Joshua H.; Nicholas, Kimberly A. (Frontiers in Environmental Science, 2017)
Vineyards shape important economic, cultural, and ecological systems in many temperate biomes. Like other agricultural systems, they can be multifunctional landscapes that not only produce grapes, but also for example serve as wildlife habitat, sequester carbon, and are places of rich traditions. However, research and management practices often focus mostly on individual, specific ecosystem services, without considering multifunctionality. Therefore, we set out to meet four research objectives: (1) evaluate how frequently the ecosystem services approach has been applied in vineyard systems; (2) identify which individual ecosystem services have been most frequently studied in vineyard systems, (3) summarize knowledge on the key ecosystem services identified in (2), and (4) illustrate approaches to multifunctionality in vineyards to inform more holistic land management. For research objective (1), we identified 45 publications that used the term “ecosystem services” in relation to vineyards, but found that only seven fully apply the ecosystem service concept to their research. For research objective (2), we operationalized the Common International Classification of Ecosystem Services (CICES) for 27 ecosystem services in vineyards, in order to consider provisioning, regulating, and cultural services through an analysis of more than 4,000 scientific papers that mentioned individual services. We found the six most frequently studied ecosystem services included (1) cultivated crop, (2) filtration, sequestration, storage and accumulation by the vineyards, (3) pest control and (4) disease control, (5) heritage, cultural and (6) scientific services. For research objective (3), we found that research on these six single ecosystem services is highly developed, but relationships between single ecosystem services are less studied. Therefore, we suggest that greater adoption of the ecosystem services approach could help scientists and practitioners to acknowledge the multifunctionality of the agricultural system and gain a holistic perspective that supports more sustainable land management.